Archeologia a Firenze : città e territorio : Atti Del Workshop, Firenze, 12-13 Aprile 2013 - D'Aquino, Valeria; D'Aquino, Valeria; Guarducci, Guido; Guarducci, Guido; Nencetti, Silvia; Nencetti, Silvia; Valentini, Stefano; Valentini, Stefano (Archaeopress archaeology, 2015)
This volume presents the proceedings of the workshop 'Archeologia a Firenze: Città e Territorio', organized by CAMNES, Centre for Ancient Mediterranean and Near Eastern Studies, in collaboration with the Soprintendenza per i Beni Archeologici della Toscana, in April 2013